Impact of Twitter on the public opinion building process: Covid 19 pandemic between March and December 2020 in Ecuador - Armijos Triviño, Norma Allyson; Zambrano Freire, Victoria Michelle (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The COVID-19 pandemic and its aftermath of deaths and illnesses gave rise in Ecuador to a conflict between the official versions published about the tragedy and those that were also made known by alternative sources, through the social network Twitter and others. The crisis caused by serious problems in the field of health revealed the important role of communication media arising from modern technologies, enabling citizen participation in the construction of media reality. Qualitative and quantitative research techniques yielded results that show how society receives contradictory information about the same facts.